Tunable electromagnetic wave-absorbing capability achieved in liquid-metal-based nanocomposite. (25th March 2019) - Ou, Meilian; Liu, Huiqiang; Chen, Xuechen; Chu, Sheng; Chu, Guang
Abstract: A Galinstan (GaInSn) liquid-metal-(LM-)based composite consisting of polydimethylsiloxane (PDMS) filled with GaInSn nanoparticles is developed for application as a tunable electromagnetic-(EM-)absorbing material. The minimum reflection loss (RL) of the GaInSn/PDMS composite is −19.3 dB at 14.8 GHz at a thickness of 2 mm, and the bandwidth over which the RL is lower than −10.0 dB is 9.9 GHz. The RL peak shifts from 14.8 GHz to 9.7 GHz under elongation by 30% shape deformation. After release, the absorption properties of the previously stretched sample almost returning to their original values suggests an approach to construct a reversibly tunable GaInSn LM-based EM-absorbing system.